ASSESSING HOSPITALITY STUDENTS’ SELF-KNOWLEDGE AND SOCIAL INFLUENCE TOWARD THEIR CAREER INTENTION - Azlina Samsudin; Amanina Mat Ghani; Malissasahila Abdul Manap; Mohd Hazrin Iman Noorkhizan; Wan Nor Bayah Wan Kamarudin (Journal of Islamic, Social, Economics and Development, 2022)
Students who understand the career insights accurately will understand their strengths and weaknesses and set clear career goals. This study includes final-year students of Hotel and Tourism Management who are required to undertake industrial attachment before graduation, as a requirement to complete their studies. Apparently, the students may have perceptions of the current economic condition due to the COVID-19 crisis, which may affect their future career prospects in the industry. This study aims to assess hospitality students’ career intentions based on self-knowledge and social influence. An online questionnaire was collected among 489 (final-year) industrial training students of Hotel and Tourism Management, and Partial Least Squares-Structural Equation Modeling (PLS-SEM) software was used to analyze the structuring of the data obtained using probability sampling. The results revealed a significant and positive effect of Self-Knowledge (SK) and Social Influence (SI) towards Career intention (CI) of hospitality students. The findings indicate that the respondents’ perceptions of career intention induced by self-knowledge and social influence provide a noteworthy insight that is relatively imperative for educators and the governance of the institutions. Finally, the differences between the respondents are summarized, and recommendations are drawn for educational institutions and further studies.